MAKING HOPSCOTCH GAME TO LEARN VOCABULARY FOR ELEMENTARY SCHOOL STUDENTS - Dyo Alvisar; A. Malik Malik (INOVISH JOURNAL, 2016)
Abstract: English is the global lesson studied in every single of education system nowadays. In fact, it is quite difficult to learn for the Indonesian people, especially for Elementary school students. One of the ways to improve their desire to learn is to combine educational elements into the game itself. This final project comes to answer that learning problem of children or elementary students by creating the alternative game. The research question was “Is there a Hopscotch Game to learn vocabulary for Elementary School Students. The purpose of the study was to make a Hopscotch Game to learn vocabulary for Elementary School Students.  The method used in this study was descriptive research. It explained the problems qualitatively to uncover solutions. The result of this study was a game which was developed from traditional games namely Hopscotch game. Application of English element in this game is the manufacturing of cards which contains some vocabulary and picture that represents the vocabulary. Therefore, surely it is easy for students to remember and to increase the number of their English vocabulary. On the other hand, they are challenged to complete all leaps in Hopscotch game while memorizing all the vocabulary that is given when they are going to jump. Then, when students make a mistake, they will get punishment which also helps to improve their vocabulary. In conclusion, maintaining the existence of traditional games and helping children to improve English vocabulary is a unique combination that is expected can be successful for students’ learning.                Keywords: Hopscotch game, Vocabulary, Elementary school students